Two Routes to Losing One’s Past Life: A Brain Trauma, an Emotional Trauma - Julie Ouellet; Isabelle Rouleau; Raymonde Labrecque; Gilles Bernier; Peter B. Scherzer (Behavioural Neurology)
Organic and psychogenic retrograde amnesia have long been considered as distinct entities and as such, studied separately. However, patterns of neuropsychological impairments in organic and psychogenic amnesia can bear interesting resemblances despite different aetiologies. In this paper, two cases with profound, selective and permanent retrograde amnesia are presented, one of an apparent organic origin and the other with an apparent psychogenic cause. The first case, DD, lost his memory after focal brain injury from a nail gun to the right temporal lobe. The second case, AC, lost her memory in the context of intense psychological suffering. In both cases, pre-morbid autobiographical memory for people, places and events was lost, and no feeling of familiarity was experienced during relearning. In addition, they both lost some semantic knowledge acquired prior to the onset of the amnesia. This contrasts with the preservation of complex motor skills without any awareness of having learned them. Both DD and AC showed mild deficits on memory tests but neither presented any anterograde amnesia. The paradox of these cases–opposite causes yet similar clinical profile–exemplifies the hypothesis that organic and psychogenic amnesia may be two expressions of the same faulty mechanism in the neural circuitry.